Mejoramiento del sistema de enfriamiento, del condensador del minichiller del laboratorio de fluidos del AEIRNNR. - Coronel Armijos, Henry Geovanny (2015)
With the development of this research was possible to propose a variant of upgrading the cooling system condenser bank of ice water cooling Fluid Laboratory. A study for the selection and implementation of a forced air-cooled condenser which fulfills the same function and heat exchange capacity, the water-cooled condenser was performed. A calculation methodology was defined to determine the area of adequate heat transfer to the condenser, where it was convenient to work with a coefficient of overall heat transfer U, which takes into account the contribution of all effects on the transfer. The refrigeration cycle analysis the heat transferred through condenser coolant was obtained. Logarithmic mean temperature between the refrigerant and the environment was employed. The condenser air forced from the catalogs of manufactures was selected, with the necessary exchange area, then we proceeded to perform an analysis with the device dimensions to determine the coefficient of both internal and external convention, plus all thermal resistances found in the heat flow path of the coolant into the air. Finally the actual overall heat transfer coefficient was obtained from the condenser. After the selection of the condenser, we proceeded with the pertinent installation of the new condenser, several processes were performed: gas welding, leak testing, vacuum testing and the system refrigerant charge. Once the installation was done temperature sensors were placed in different strategic points that allow to take data and then graphing the refrigeration cycle.